Renal Artery : Variations and It’s Clinical Significance - manju (GMC Patiala Journal of Research and Medical Education, 2024)
Anatomy of renal artery and its variations is well known in literature. Anatomical variations in renal vessels have significant importance in diagnostic and therapeutic procedures. Knowledge of Accessory or aberrant renal artery is important for performing endovascular ,radiological, laparoscopic procedures and surgical interventions in transplants, nephrectomies and renal vascular disorders. The present study was conducted in department of anatomy Govt. medical college Patiala ,India during routine abdominal dissection for medical undergraduate students. Kidneys along with its arteries were exposed in 13 cadavers (12 males and 1 female). Variation in the form of accessory renal artery was found in two cadavers. Knowledge of variations in renal vasculature is important for clinicians uroradiological procedures and renal surgeries.